Job satisfaction and turnover intention among technical employees in quantity surveying firms - Nik Nur Azirah binti Mohamed Nor (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2016)
Human resource is the key component for organizational success. It is crucial for organizations to manage their human resources effectively in order to avoid them from leaving the organizations. Job satisfaction is identified as one of the factors that cause turnover intention of employees. The objectives of this study are to determine the level of job satisfaction among technical employees of Quantity Surveying firms, examine the relationship between job satisfaction and turnover intention of technical employees in the Quantity Surveying firms and suggest strategies to increase job satisfaction and reduce their turnover intention. Questionnaire surveys and interviews were employed to obtain the data required. A total number of 183 respondents responded to the questionnaires and data obtained were analyzed by using Statistical Package for Social Science (SPSS Window) Version 21.0. Descriptive and inferential analyses were used to analyze the data obtained from the questionnaire survey while the test of Mann – Whitney U has been employed for hypothesis testing. The interviews were conducted with five (5) Quantity Surveying firms and data obtained were analyzed using the content analysis. The findings of the studies have identified that many of the technical employees in Quantity Surveying firms are satisfied on most of the items on the constructs of nature of work, working relationship with immediate superior, organizational factors, social interaction and attitude towards work. The findings also reveal that there is relationship between turnover intention and job satisfaction on the constructs of opportunities and rewards, nature of work, working relationship with immediate superior and organizational factors. Various strategies are suggested to increase the job satisfaction of the technical employees in Quantity Surveying firms and to reduce their turnover intention. The strategies are to enhance reward system to increase job satisfaction on the construct of opportunities and rewards, enrich work context to enhance job satisfaction on the construct of nature of work, strengthen superior-subordinate relationship to increase the level of job satisfaction on the construct of working relationship with immediate superior, improve working physical environment to enhance job satisfaction on the construct of organizational factors and organize incentive programs to educate employees on the importance of establishing positive relationship with colleagues to increase job satisfaction on the construct of social interaction. Therefore, enhancement of job satisfaction should be highlighted by organizations to reduce turnover intention of the employees.